The Influence Of Social Media Marketing And Characteristics Of Buyers On The Decision To Purchase Sony Mirrorless Camera In Bogor City - Agref Valendra Putra; Sufrin Hannan; Yuary Farradia (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
This research aims to determine and analyze the influence of social media marketing and characteristics of buyers on purchasing decisions for Sony Mirrorless Cameras in Bogor City through purchase interest as an intervening variable. This research method is quantitative research with a sample size of 319 people. The research results show that Social Media Marketing has a Charachter of Buyingitive and significant effect on Purchase Decisions, mediated by Purchase Interest. Characteristics of Buyer has a Charachter of Buyingitive and significant effect on Purchase Decisions mediated by Purchase Interest. Improving Purchasing Decisions emphasizes building trust between producers and consumers. The existence of mutual trust between producers and consumers will create good conditions for the exchange of information and advice without fear. In other words, trust is a central issue in human civilization. The influence of trust is so central because this character also occupies important purchasing decisions.